2021
DOI: 10.1158/1078-0432.ccr-21-3231
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of ctDNA in Patients with Breast Cancer During Neoadjuvant Treatment Is a Significant Predictor of Poor Tumor Response

Abstract: Accurate response assessment during neoadjuvant systemic treatment (NST) poses a clinical challenge. Therefore, a minimally-invasive assessment of tumor response based on cell-free circulating tumor DNA (ctDNA) may be beneficial to guide treatment decisions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
0
24
2
Order By: Relevance
“…Combining CTC-enumeration with the detection of circulating tumor DNA (ctDNA), shed by tumors during apoptosis, might overcome this problem and considerably increase sensitivity. The prognostic relevance of ctDNA in early breast cancer has been demonstrated in several studies [ 54 , 55 ]. Furthermore, the detection of molecular relapse during breast cancer follow-up via personalized ctDNA profiling has generated a lead-time preceding the clinical detection of metastasis for up to two years.…”
Section: Discussionmentioning
confidence: 99%
“…Combining CTC-enumeration with the detection of circulating tumor DNA (ctDNA), shed by tumors during apoptosis, might overcome this problem and considerably increase sensitivity. The prognostic relevance of ctDNA in early breast cancer has been demonstrated in several studies [ 54 , 55 ]. Furthermore, the detection of molecular relapse during breast cancer follow-up via personalized ctDNA profiling has generated a lead-time preceding the clinical detection of metastasis for up to two years.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, monitoring tumor dynamics with ctDNA during and after NAT has great potential because it could guide post-NAT management in several ways, including escalation/de-escalation of NAT or adjuvant therapy; delaying or omitting surgery ("watch-and-wait" or non-operative management [NOM]). In fact, positive ctDNA MRD during or after NAT was associated with an increased recurrence risk in locally advanced breast, rectal, gastric/gastroesophageal, and esophageal cancer, as well as in resectable CRC liver metastases, and even outperformed imaging in a few studies [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Recent randomized CheckMate-816 and I-SPY 2 are representative studies demonstrating the potential utility of ctDNA in NAT [90,101].…”
Section: Treatment Monitoring During Neoadjuvant Treatmentmentioning
confidence: 99%
“…After a median follow-up of 4.8 years for survival analysis, this study showed that non-pCR patients positive for ctDNA at T3 have an increased risk of metastatic relapse in comparison with those who were also non-pCR but were ctDNA-negative at T3, who had excellent outcomes [ 137 ]. Zhou et al also evaluated ctDNA in 145 patients and demonstrated that the persistence of ctDNA during the treatment was correlated with non-response to NAC (Residual Cancer Burden of II/III) [ 148 ].…”
Section: Predictive Biomarkers Under Investigationmentioning
confidence: 99%